Combination Therapy of Radiofrequency Ablation and Transarterial Chemoembolization for Unresectable Hepatocellular Carcinoma: A Retrospective Study. Issue 20 (May 2016) - Tang, Chengwu; Shen, Jian; Feng, Wenming; Bao, Ying; Dong, Xiaogang; Dai, Yi; Zheng, Yinyuan; Zhang, Jianping
Abstract : Abstract: The treatment efficacy of unresectable hepatocellular carcinoma (HCC) is still not promising. This study aimed to compare the efficacy and safety of radiofrequency ablation (RFA) combined with transarterial chemoembolization (TACE) for unresectable HCC with a single treatment. Between June 2009 and June 2012, 132 patients who were diagnosed with unresectable HCC and accepted nonsurgical treatments in our center were enrolled in this retrospective study. On the basis of treatment modality, they were allocated to 3 groups: 49 patients accepted RFA (RFA group); 43 patients accepted TACE (TACE group); and 40 patients accepted RFA following TACE (combination group). Clinical data including complications, treatment success rate, hospitalization costs, intrahepatic recurrence-free survival, overall survival, and factors influencing survival were retrospectively analyzed. Patient characteristics between these groups showed no significant difference. Treatment success was achieved in all patients of 3 groups. The combination group had a significantly higher total hospitalization cost to treatment than the TACE group (63, 708.14 ± 9193.81 Chinese yuan vs 37, 534.88 ± 6802.84 Chinese yuan; P  = 0.0000). All complications were controllable and no permanent adverse sequelae or procedure-related deaths were observed. The 3-year intrahepatic recurrence-free survival probability was significantly better in the combination group than in the TACE group (42.50% vs 20.93%; hazard ratio [HR], 0.5105; 95% confidence interval [CI], 0.3022–0.8625; P  = 0.0094) or the RFA group (42.50% vs 22.45%; HR, 0.5233; 95% CI, 0.3149–0.8697; P  = 0.0111).The 3-year overall survival probability was significantly better in the combination group than in the TACE group (45.00% vs 26.53%; HR, 0.5069; 95% CI, 0.2936–0.8752; P  = 0.0100) or the RFA group (45.00% vs 27.91%; HR, 0.4913; 95% CI, 0.2928–0.8246; P  = 0.0054). Main tumor size, number of tumors, and treatment modality were demonstrated to be important factors associated with 3-year intrahepatic recurrence-free survival probability and overall survival probability ( P  < 0.05) by univariate and multivariate analyses. Combination therapy of RFA and TACE was superior to TACE alone or RFA alone in improving survival for patients with unresectable HCC.